Review of Current Trends in Vaccine Development against Zoonotic Viruses: Challenges and Innovations - Priyanshu Upadhyay (International Journal of Virus Studies, 2024)
The emergence of zoonotic viruses poses a significant threat to global public health, necessitating rapid advancements in vaccine development. This review highlights the current trends and innovative strategies employed in the creation of vaccines against zoonotic pathogens, including but not limited to viruses responsible for diseases such as Ebola, Zika, Nipah, and more recently, SARS-CoV-2. We discuss various vaccine platforms, including inactivated, live attenuated, mRNA, and viral vector vaccines, focusing on their effectiveness, safety profiles, and deployment challenges. The review also addresses the complexities associated with vaccine development, such as the need for rapid responses to outbreaks, the role of preclinical studies, and the importance of international collaboration. Zoonotic viruses, responsible for numerous recent epidemics, highlight the critical necessity of proactive and pre-emptive approaches in vaccine research, development, and distribution. Furthermore, we examine innovative approaches like nanoparticle delivery systems and recombinant vaccines that have emerged in response to evolving zoonotic threats. The findings underscore the importance of a multidisciplinary approach to vaccine development, integrating technological advancements, ecological surveillance, and public health initiatives to combat zoonotic diseases effectively.
Keywords: Zoonotic viruses; disease outbreaks; global health collaboration; innovations in immunization; mRNA vaccines; nanoparticle delivery systems; public health; vaccine development; vaccine platforms; viral vector vaccines